First report of lice infestation among saanen goats in Kuantan, Malaysia - Mat Yusof, Afzan (Academic Journals Inc., USA, 2018)
Background and Objective: Ectoparasites remains as one of major challenges in goat farming industry. They are ubiquitous and often cause harmful effects on livestock production and productivity. Ectoparasites give rise to morbidity and mortality among goat population which consequently lead to reductions in meat and milk. This study was conducted to identify and determine the risk factors of ectoparasitic infestations among Saanen goats in Kuantan, Malaysia. Materials and Methods: A total of 30 goats were inspected for the presence of ectoparasitic infestations. The infested ectoparasites were collected through hand-picked and brushing methods. The collected ectoparasites were preserved in 70% ethanol. The counting of ectoparasites was done by using light microscope. The number of ectoparasites were counted and analyzed by Chi-square(x2) test. Results: The results show that the lice were the only ectoparasite found in all 30 goats. The lice infestation was significantly associated with the age and sex factors of goats. Female goats were infested with lice with higher percentage of lice (51.6%, n=372) than male goats (48.4%, n=349). With regard to age factor, young goats were more susceptible to lice infestation than adult goats with the percentage of lice (67%, n= 483) and (33%, n=238), respectively. The predilection site of lice infestation was mostly found on the body region of goats. Conclusion: Good sanitary condition and proper ectoparasite control are needed to reduce the transmission of ectoparasites in goat herds.